Comparing onsite and offsite rail access for dry port developments – A benchmark study in China. (June 2020) - Wang, Yuhong; Monios, Jason; Zhang, Mengjie
Abstract: While large dry ports with high throughput are more likely to have onsite rail access, the question is more difficult for small and medium sites, which may not have sufficient throughput for rail viability. Thus whether a new dry port development should be located with or without direct rail access is a major concern at the proposal stage. This challenge is a current concern in many developing countries experiencing a surge in dry port demand. The aim of this paper is to develop a model that can identify at what level of demand the onsite configuration becomes the better option. The model calculates the equilibrium point in total costs between onsite and offsite dry ports, which varies according to changes in land price, operational productivity and modal split. Taking China as an example case, findings suggest that the land cost plays a vital role in the decision of an onsite or offsite configuration. The modal split of the cargo using the dry port, which is greatly affected by shipping distance to seaports and shipper preference, also shows a strong effect on the decision.